2021
DOI: 10.2106/jbjs.oa.20.00091
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Risk Prediction Models for Short-Term Revision and Death After Total Hip Arthroplasty

Abstract: Background: Because of the increasing number of total hip arthroplasties (THAs), even a small proportion of complications after the operation can lead to substantial individual difficulties and health-care costs. The aim of this study was to develop simple-to-use risk prediction models to assess the risk of the most common reasons for implant failure to facilitate clinical decision-making and to ensure long-term survival of primary THAs. Methods: We analyzed patient and sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…The improved performance is explained by the different input variables resulting from the applied iterative variable selection procedure used successfully also before. 22 , 23 , 24 Alternatively, poorly adjusted regression coefficients due to inherent differences between patient populations and local healthcare practices or overfitting may explain the worse performance of previous models. For example, the Lyman model had drastically different coefficients for different treatment regimens compared to Lasso and Li models (Table 2 , Table S1 ) which might explain its underperformance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The improved performance is explained by the different input variables resulting from the applied iterative variable selection procedure used successfully also before. 22 , 23 , 24 Alternatively, poorly adjusted regression coefficients due to inherent differences between patient populations and local healthcare practices or overfitting may explain the worse performance of previous models. For example, the Lyman model had drastically different coefficients for different treatment regimens compared to Lasso and Li models (Table 2 , Table S1 ) which might explain its underperformance.…”
Section: Discussionmentioning
confidence: 99%
“…The improved performance is explained by the different input variables resulting from the applied iterative variable selection procedure used successfully also before 22‐24 . Alternatively, poorly adjusted regression coefficients due to inherent differences between patient populations and local healthcare practices or overfitting may explain the worse performance of previous models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, a relatively low number of iterations would lead to not covering all binning arrangements. In practice, we have observed that 100 iterations is sufficient for obtaining a stable set of features in a range of datasets ( Klén et al , 2019 , 2020 ; Venäläinen et al , 2020 , 2021 ).…”
Section: Methodsmentioning
confidence: 99%